Hubungan Status Gizi, Asupan Energi, dan Beban Kerja Terhadap Kelelahan Subjektif Pekerja Dapur Makan Gratis - Alifia Nugraheni; Tesa Rafkhani (Universitas Airlangga, 2026)
Background: The free meal kitchen is a unit responsible for implementing the free meal program, the success of which depends on workers’ roles. Free meal kitchen workers are required to engage in physical activity and high levels of concentration to ensure the effective implementation of the program. Continuous work activities can increase workload, and if not balanced with nutritional status and adequate energy intake, they may increase the risk of fatigue. According to the International Labour Organization, approximately 32% of workers globally have experienced work fatigue, with 18.3% and 27% reporting moderate and high fatigue, respectively (ILO, 2016). Objectives: This study aimed to determine the relationships between nutritional status, energy intake, and workload with subjective fatigue among workers in free meal kitchens. Methods: This research used a descriptive correlational design and a cross-sectional method. This research used a purposive sampling technique with 40 respondents. Nutritional status was assessed using Body Mass Index (BMI), energy intake using 3×24-hour dietary recall, workload using the NASA-TLX (National Aeronautics and Space Administration Task Load Index) questionnaire, and subjective fatigue using the KAUPK2 (Kuesioner Alat Ukur Perasaan Kelelahan Kerja) questionnaire. The data were analyzed using the Spearman-rank test. Results: This research showed that Energy intake (p=0.392) did not correlate with subjective fatigue. Nutritional status (p=0.027) and workload (p=0.009) were significantly correlated with subjective fatigue among workers in the free-meal kitchens. Conclusion: This study shows that subjective fatigue is more related to nutritional status and workload than energy intake. The author recommends that free meal kitchens evaluate their workload and monitor nutritional status and food intake to reduce the risk of higher work fatigue.